Utilizing Carvalho's Framework for Media Discourse Analysis: A Critical Discourse Analysis of Print Media News Headlines - Shah, Muhammad Mubeen (Annals of Human and Social Sciences, 2025)
Analyzing mediated communication is a common practice among research students, with multiple frameworks used for such analyses. The current study aims to present the application of Carvalho’s (2008) framework, focusing on textual and contextual analysis. The nature of the study is qualitative. Four headlines were selected from Daily Jang for analysis using a simple random sampling technique, covering political, economic, and entertainment categories. The key findings reveal that Carvalho’s framework could be a valuable choice for analyzing journalistic content. In addition, the results show that text and context are interlinked in print media headlines, where content creators use specific designs and strategic language by making certain linguistic choices to achieve communication goals. This research could provide a significant roadmap for linguistic and journalism students who intend to pursue their research in Critical Discourse Analysis (CDA). They may gain insight into how text is analysed through the lens of Carvalho’s framework.